Energy and exergy analysis of a novel ejector-absorption combined refrigeration cycle using natural refrigerants. (13th September 2022) - Verma, Abhishek; Kaushik, S.C.; Tyagi, S.K.
This article presents the theoretical analysis of a unique ejector-absorption combined refrigeration system for producing low-temperature refrigeration at -25°C and additional cooling at a temperature of 7°C by utilising the waste heat. The additional cooling is achieved by combining a trans-critical CO2 ejector refrigeration cycle with an absorption system using LiBr-H2 O as the working fluid pair and is powered by waste heat from the gas cooler of the ejector cycle. The energy and exergy analyses have been carried out for a typical set of operating conditions to maximise the performance of the combined system. The performance of the combined system was compared to that of the basic trans-critical CO2 ejector refrigeration cycle. The study shows a significant improvement in the performance of the system, the increment in COP and exergy efficiency was found to be 16.36% and 4.134%, respectively.